INTEGRATION OF ETHNOMATHEMATICS IN STRENGTHENING HIGH SCHOOL STUDENTS' NUMERACY LITERACY - Herwandi Sape; Agustan Syamsuddin; Nasrun; Muh. Fachrullah Amal (Jurnal Penalaran dan Riset Matematika, 2026)
This study aims to analyze the integration of ethnomathematics in strengthening students’ numeracy literacy at SMA Negeri 3 Maros. The study was motivated by the low level of students’ numeracy literacy, which remains a major challenge in mathematics learning, particularly in understanding and solving contextual problems. Ethnomathematics is considered a relevant learning approach because it connects mathematical concepts with local cultural contexts, making learning more contextual and meaningful. This study employed a descriptive qualitative approach. The research subjects consisted of 32 students who completed a Likert-scale questionnaire, 3 students who participated in in-depth interviews, and 1 mathematics teacher who was also interviewed. Data collection techniques included questionnaires and in-depth interviews. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings revealed that the integration of ethnomathematics contributed positively to strengthening students’ numeracy literacy. A total of 84.3% of students stated that the use of local cultural contexts helped them understand the use of mathematical numbers and symbols in daily life, while 81.2% reported that they found it easier to analyze contextual mathematical problems when learning activities were linked to local culture. Interview results also indicated that ethnomathematics-based learning helped students understand mathematical concepts more concretely, improved their ability to solve numeracy problems, and enhanced their ability to interpret and communicate mathematical problem-solving processes. Furthermore, the mathematics teacher stated that integrating local culture into mathematics learning increased students’ participation and engagement during the learning process.